Ultrasonido de baja intensidad para el tratamiento de fracturas óseas con retardo en la curación - Rodríguez Rúa, Orlando R.; Monreal, Ricardo; Chong-Quero, J. Enrique (Revista Mexicana de Ingenieria Biomedica, 2005)
The employment of a low intensity pulsed ultrasound signal has been demonstrating through numerous clinical studies, to be an effective method for the stimulation of bone repair. This work presents the results obtained in a preliminary study realized in the “Manuel Fajardo Teaching Hospital”, in Havana, Cuba, between 1999 and 2000, about the treatment of bone fractures with a delayed healing process treated by a specific ultrasound therapy. A total of 11 fractures with different times of evolution were treated daily for a period of 20 minutes, with an ultrasound signal of 30 mW/cm2 (spatial average - temporal average), 1 MHz, 400 µs sine wave burst width, repeated at 0.5 kHz. The treatment was employed until the fracture was found clinically and radiologically healed. No treatment failed.